Land-use change and habitat fragmentation of Leopardus pardalis in Highlands of Puebla, Mexico - Hernández-Pérez, Ezequiel; Lemos Rincón, Sergio Gilmar; Ayala-Hernández, María M.; Aleman-Sancheschúlz, Gilberto (THERYA, 2024)
Ocelots are relatively tolerant to habitat modification. However, it has been observed that they may be sensitive to habitat loss and fragmentation as a result of human development. The Sierra Norte de Puebla is considered a potential habitat for ocelots and other tropical felines. However, it has suffered heavy loss and fragmentation of its natural ecosystems, which considerably affects habitat availability and quality. This study analyzed the land-use changes and habitat fragmentation in the distribution range of the ocelot in the Sierra Norte de Puebla, Mexico, from 1993 to 2020. Habitat suitability was determined using potential distribution models and vegetation and land-use maps from 1993, 2003, and 2020, obtained using supervised classification of Landsat images. The resulting maps were reclassified in terms of the habitat suitability for Leopardus pardalis according to their quality. Land-use changes and habitat loss were quantified with a transition matrix, and fragmentation was assessed using the Morphological Spatial Pattern Analysis tool of the program GUIDOS. These habitat fragments were quantified using the integral index of connectivity with the CONEFOR Sensinode program. We estimated that 22.2 % of the study area has suitable conditions for ocelots. From 1993 to 2020, the area covered by natural vegetation decreased 16 % at an annual rate of -2.4 %. During this period, the mean fragment size and shape index decreased; on the other hand, the number of fragments and the Euclidean distance between fragments increased. The percentages of edge, branch, and islet vegetation dropped from 1993 to 2003 but increased in 2020. The connectivity analysis indicated that two habitat fragments showed high values of the integral index of connectivity. The increase in anthropogenic cover and the habitat loss for L. pardalis between 1993 and 2020 affected mainly vegetation fragments considered optimal for the persistence of this species. In these ecosystems, agricultural and livestock practices are expanding vigorously, increasing edge habitats and decreasing the core area of habitat fragments. The areas that recorded the presence of ocelots have optimum conditions to serve as biological corridors in the Sierra Madre Oriental, particularly in the portion of the Sierra Norte de Puebla. The fragmentation of the ocelot habitat is of particular concern and should be addressed strategically for the long-term conservation of the ocelot and regional biodiversity.